Stabilization and savings funds to manage natural resource revenues: Kazakhstan and Azerbaijan vs. Norway - Matthias Lücke (Kiel Institute for the World Economy (IfW), 2010)
Do the sovereign wealth funds of Kazakhstan and Azerbaijan promote the sustainable use of government oil revenues? We review the operational rules and performance of the two funds and compare them to Norway's Government Pension Fund Global. The key challenges are to stabilize government expenditures despite volatile resource prices, build up a capital stock to draw on after the resource is depleted, and to save and spend resource revenues transparently. We conclude that the institutional framework of a resource fund may indeed enhance transparency and public scrutiny, limit discretionary control, and sustain public support for long-term savings of resource revenues.
Keywords: O13; Q32; L71; 330; resource-based development; sovereign wealth fund; Staatsfonds; Finanzpolitik; Sparen; Nachhaltigkeit; Rohstoffpreis; Exporterlös; Vergleich; Aserbaidschan; Kasachstan; Norwegen